CDK1 couples proliferation with protein synthesis [repository tables R1-R4] - Hörth, Katharina; Stoecklin, Georg (Universität, 2020)
Cell proliferation exerts a high demand on protein synthesis, yet the mechanisms coupling the two processes are not fully understood. A kinase and ...
Gesehen am 06.02.2020
Keywords: Forschungsdaten; Datenbank